Research in performing arts: the dilemmas of method, the challenges of writing and the relationship between art and pain in dance (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This work aimed to think and reflect on the field shaped by academic research in performing arts today, from three perspectives: the dilemmas faced by researchers regarding methodological guidelines, which sometimes reflect the difficulties in producing and mobilizing so-called scientific knowledge in the arts field; the clash with scholastic paradigms that still permeate the construction of knowledge in universities; and finally, the challenges posed by the painful exercise of attempting to write about the body in the art of dance.
Keywords: dance; method; body; art and pain; dance writting